Molecular organization of 5S rDNA in sharks of the genus Rhizoprionodon: insights into the evolutionary dynamics of 5S rDNA in vertebrate genomes - Pinhal, Danillo [UNESP]; Arak, Carlos S. [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP]; Martins, Cesar [UNESP] (Cambridge University Press, 2009)
In this Study, we attempted a molecular characterization of the 5S rDNA in two closely related species of carcharhiniform sharks, Rhizoprionodon lalandii and Rhizoprionodon porosus, as well as a further comparative analysis of available data on lampreys, several fish groups and other vertebrates. Our data show that Rhizoprionodon sharks carry two 5S rDNA classes in their genomes: a short repeat class (termed class I) composed of similar to 185 bp repeats, and a large repeat class (termed class II) arrayed in similar to 465 bp units. These classes were differentiated by several base Substitutions in the 5S coding region and by completely distinct non-transcribed spacers (NTS). In class II, both species showed a similar composition for both the gene coding region and the NTS region. In contrast, class I varied extensively both within and between the two shark species. A comparative analysis of 5S rRNA gene sequences of elasmobranchs and other vertebrates showed that class I is closely related to the bony fishes, whereas the class II gene formed a separate cartilaginous clade. The presence of two variant classes of 5S rDNA in sharks likely maintains the tendency for dual ribosomal classes observed in other fish species. The present data regarding the 5S rDNA organization provide insights into the dynamics and evolution of this multigene family in the fish genome, and they may also be useful in clarifying aspects of vertebrate genome evolution.